(untitled) (Pedagogy of Higher and Secondary Education, 2016)
Stupnik M. I., Morkun V. S., Bakum Z. P., Tkachuk V. V. The concept of a mining engineer training in the lifelong learning system (school − higher educational institution − enterprise). In the article the concept of a mining engineer training in the lifelong learning system has been developed. The attention is focused on the fact that among urgent problems the effective training and professional development of mining engineers are of key importance because of a severe shortage of highly qualified mining professionals. Stages of training have been defined. They are general educational institution, higher educational institution, enterprise. The value of occupational guidance, didactic principles of future engineers training in the condition of modern university have been proved. The problems of adaptation of mining faculty graduates at the enterprise have been discussed. The first stage in the system of mining engineer training is educational institutions where one of the main objectives is ensuring the social adaptation of students, their adjustment to real conditions of society, existing structure of social relations and activities, including work activity. The occupational guidance as an important factor providing the involvement of prospective students to further training at mining faculties has been described. It includes not only the information about professions, but work activity requirements as well. The next stage, the finding out didactic principles of mining specialists training in terms of higher education, should be considered. It is noted that the educational process is carried out at two levels. At the bachelor course students acquire knowledge of humanities, social-economic, mathematical, natural science and general professional disciplines. At the same time they study special disciplines (from the cycle of general engineering and practical training). The second stage, engineering training according to specialty, involves profound studying of mining laws, economics and management, mining and blasting safety, and their design using modern computer systems. At the final stage in the system of mining engineer training the adaptation of mining faculty graduates in the conditions of the modern enterprise has been characterized. It is difficult for young specialists because it is connected with significant change of purpose, conditions of activity, social environment, status and roles.